Konseling Pastoral Kedukaan - Thony Ronaldo Nugroho; Yanto Paulus Hermanto (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
The event of death can lead to sorrow or grief, which is an emotional response to the loss experienced by someone due to the passing of a loved one. One of the ministries that a church can provide to grieving members is through the approach of pastoral grief counseling. The research was conducted using a qualitative method, namely a literature review. From the research results, it was found that effective pastoral grief counseling can be built based on the stages of grief by Kubler Ross, which are Denial, Anger, Bargaining, Depression, and Acceptance. Through this approach, church members can be helped to go through a healthy grieving process, so that ultimately those who are mourning do not experience negative impacts from the grief they are going through.